Use of sockets in computing: A Systematic Review of the literature: Systematic Literature Review: Use of Sockets in Computer Science. (Innovation & Development in Engineering and Applied Science, 2021)
Sockets in the area of ​​computing are a technological alternative proposed as an efficient communication mechanism between applications that work under the client-server architecture, they can be applied in different areas related to computing. This article refers to a systematic literature review (SLR) in order to obtain sufficient information on the different uses or applications of sockets in computer science areas for further analysis. For this, the selection of reliable bibliographic sources is made where relevant information was obtained from articles in validated scientific journals with a quality impact factor, obtaining as a result that the use of sockets improves the flow of information and when applied in the different Technological areas such as: Artificial intelligence, computer security, software architectures, web services, operating systems and communication networks have a positive influence, improving their performance, all this is demonstrated in a matrix of applications in the same way a matrix was developed of advantages of use, which allowed to conclude that the sockets are versatile and viable to be applied in the different technological areas in addition to generating a series of advantages
Keywords: connectors, systems, software architecture, communication, sockets